Aquaculture network for Africa (ANAF) strategy 2025 – 2029 - AU-IBAR (AU-IBAR, 2025)
The formation of the Aquaculture Network for Africa (ANAF) emanated as a recommendation of the Fish for All Summit that was held in Abuja, Nigeria in 2005. The Fish for All Summit was organized by the AUC-NEPAD (now AUDA-NEPAD) in response to the dismal status of Africa’s fishery sector. Natural fish stocks had plummeted below their sustainable limits which was largely artisanal fishing communities, food and nutrition security and the sectors contribution towards national earnings. The continent’s average per capita fish consumption rates were steadily falling below global averages. Africa consequently became a net importer of food fish. Compounded by unsustainable fishery management practices, weak sectoral governance, Illegal Unreported and Unregulated (IUU) fishing, environmental degradation and climate-change and population growth, the prospects for reversing and transforming the sector into one that could sustainably contribute towards the continent’s development goals grew weaker.